A low-surface-energy uv-cured pressure-sensitive adhesive and its preparation method and application
Patent Information
- Application Number
- CN202411829854.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-12-12
AI Technical Summary
然而,这些预处理过程不仅增加了工艺复杂性,还导致了额外的成本,从而限制了低表面能塑料的广泛应用
[0024]本发明通过引入聚乙二醇改性丙烯酸酯单体,对压敏胶的分子结构进行了优化,从而提升了其与基材的附着力和内聚力。在压敏胶的分子设计中,加入了低表面能有机硅改性丙烯酸酯,这显著增强了对低表面能材料的粘接性能。同时,通过引入交联剂,进一步提升了内聚强度,有效改善了持黏力。总体而言,本发明在保留现有UV固化技术优势的基础上,通过分子设计显著增强了对低表面能材料的黏附性能,进而大幅提升了UV压敏胶的整体性能及应用范围。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of adhesives, specifically relating to a low surface energy UV-curable pressure-sensitive adhesive for bonding, its preparation method, and its application. Background Technology
[0002] In recent years, bonding technologies for low surface energy plastics (such as polyethylene, isotropic polypropylene, and polytetrafluoroethylene) have faced challenges, often requiring surface pretreatment to increase their surface energy and thus promote molecular-level interactions between the adhesive and the substrate. Common pretreatment methods include corona treatment, plasma treatment, flame treatment, and applying a compatible polymer solution (primer) to cause the polymer surface to swell and achieve chain entanglement with the plastic substrate. However, these pretreatment processes not only increase process complexity but also lead to additional costs, thus limiting the widespread application of low surface energy plastics.
[0003] Furthermore, while traditional pressure-sensitive adhesives offer advantages such as low equipment investment, low cost, and environmental friendliness, their adhesion performance to low surface energy materials remains insufficient. For example, they exhibit poor adhesion to non-polar plastics such as polypropylene, polyethylene, ethylene-propylene diene rubber, and polytetrafluoroethylene. This issue significantly limits the application potential of these materials in industries such as automotive, furniture, and construction. Therefore, developing a novel UV-curable pressure-sensitive adhesive for low surface energy adhesion has become an important task in improving the current technological status of this field. Summary of the Invention
[0004] To overcome the shortcomings and deficiencies of existing technologies, the primary objective of this invention is to provide a UV-curable pressure-sensitive adhesive for low surface energy adhesion. The main raw materials of this pressure-sensitive adhesive are acrylate copolymers prepared from silicone-modified acrylates, polyethylene glycol-modified acrylates, and other acrylate monomers. While maintaining the advantages of existing UV curing technologies, this pressure-sensitive adhesive significantly enhances its adhesion performance to low surface energy materials, thereby greatly improving the overall performance and application range of UV pressure-sensitive adhesives.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned low surface energy UV-curable pressure-sensitive adhesive.
[0006] Another object of the present invention is to provide the application of the above-mentioned low surface energy adhesive for UV curing pressure sensitivity.
[0007] The objective of this invention is achieved through the following technical solution:
[0008] A low surface energy UV-curable pressure-sensitive adhesive is prepared from the following raw materials: 100 parts by weight of acrylate copolymer raw material, 0.2-2 parts by weight of photoinitiator, 0.1-2 parts by weight of n-dodecyl mercaptan, 0.3-1.5 parts by weight of azobisisobutyronitrile, 0.5-2.5 parts by weight of crosslinking agent, and 70-100 parts by weight of ethyl acetate; wherein the 100 parts by weight of acrylate copolymer raw material is composed of 60-85 parts by weight of soft monomer, 5-15 parts by weight of hard monomer, 1-10 parts by weight of functional monomer, 1-10 parts by weight of silicone-modified acrylate, and 1-10 parts by weight of polyethylene glycol-modified acrylate.
[0009] The soft monomer is one or a mixture of isooctyl acrylate, butyl acrylate and 2-ethylhexyl acrylate;
[0010] The hard monomer is one or more of methyl acrylate, methyl methacrylate, ethyl methacrylate, vinyl acetate, and 2-phenoxyethyl acrylate;
[0011] The functional monomer is one or a mixture of two of acrylic acid and methacrylic acid.
[0012] The organosilicon-modified acrylate is one or a mixture of more of the following: 3-(methacryloyloxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltriethoxysilane, 3-(trimethoxysilyl)acrylate, 3-[tris(trimethylsiloxy)silyl]propyl methacrylate, and (3-acryloyloxypropyl)tris(trimethylsiloxy)silane.
[0013] The polyethylene glycol-modified acrylate has a molecular weight ≤2000, and is specifically one or a mixture of polyethylene glycol acrylate, polyethylene glycol methacrylate, polyethylene glycol methyl ether methacrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol ethoxyacrylate, and polyethylene glycol ethoxymethacrylate.
[0014] The crosslinking agent is one or a mixture of more of the following: diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol dimethacrylate, and tetraethylene glycol diacrylate.
[0015] The photoinitiator is one or a mixture of two of 4-acryloyloxybenzophenone, 4-acryloyloxyethoxybenzophenone, and 4-acryloyloxy-2-hydroxybenzophenone.
[0016] The above-mentioned method for preparing a low surface energy UV-curable pressure-sensitive adhesive includes the following steps:
[0017] (1) Weigh 60-85 parts by weight of soft monomer, 5-15 parts by weight of hard monomer, 1-10 parts by weight of functional monomer, 1-10 parts by weight of organosilicon-modified acrylate, 1-10 parts by weight of polyethylene glycol-modified acrylate, 0.2-2 parts by weight of photoinitiator, 0.1-2 parts by weight of n-dodecyl mercaptan, 0.3-1.5 parts by weight of azobisisobutyronitrile, 0.5-2.5 parts by weight of crosslinking agent and mix them evenly with 70-100 parts by weight of ethyl acetate to obtain a mixture;
[0018] (2) Add the mixture to the reactor at a uniform rate, raise the temperature to 65-90℃ to carry out free radical initiation polymerization, and after the addition is completed, keep the temperature at 75-90℃ for 2-5 hours to obtain a polymer solution.
[0019] (3) The polymer solution was subjected to vacuum distillation at 120-150°C to remove ethyl acetate, resulting in a low surface energy UV-curable pressure-sensitive adhesive.
[0020] The above-mentioned low surface energy UV-curable pressure-sensitive adhesive is used in hot melt pressure-sensitive adhesive tape products.
[0021] The low surface energy adhesive UV-curable pressure-sensitive adhesive is hot-melted at 100–140℃, and then applied at a rate of 20–65 g / m². 2 The coating amount is applied to the thin film substrate and cured by irradiation with a 200-408nm ultraviolet light source to obtain a low surface energy UV-curable pressure-sensitive adhesive tape product.
[0022] The film substrate is a film-type substrate such as PET film or BOPP film.
[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0024] This invention optimizes the molecular structure of pressure-sensitive adhesives by introducing polyethylene glycol-modified acrylate monomers, thereby enhancing their adhesion and cohesive strength to substrates. The inclusion of low-surface-energy silicone-modified acrylates in the molecular design significantly improves adhesion to low-surface-energy materials. Simultaneously, the introduction of a crosslinking agent further enhances cohesive strength and effectively improves holding power. Overall, this invention, while retaining the advantages of existing UV curing technologies, significantly enhances adhesion to low-surface-energy materials through molecular design, thereby substantially improving the overall performance and application range of UV pressure-sensitive adhesives. Detailed Implementation
[0025] The present invention will be further described in detail below with reference to the embodiments, but the implementation of the present invention is not limited thereto. Experimental methods that do not specify specific conditions in the embodiments are carried out according to conventional methods and conditions.
[0026] Method for determining initial tack: The ring initial tack test of PET pressure-sensitive tape shall be conducted in accordance with GB / T 31125-2014.
[0027] Method for determining peel strength: The peel strength of PET pressure-sensitive tape is tested using a tensile testing machine according to GB / T2792-2014.
[0028] Method for determining holding power: The holding power of PET pressure-sensitive tape was tested according to GB / T4851-2014.
[0029] Example 1:
[0030] (1) Mix 60g of isooctyl acrylate, 20g of butyl acrylate, 4.5g of acrylic acid, 5g of methyl methacrylate, 4.5g of methyl acrylate, 5.0g of polyethylene glycol methyl ether acrylate (molecular weight 800), 1.0g of 3-(methacryloyloxy)propyltriethoxysilane, 0.5g of n-dodecyl mercaptan, 0.5g of 4-acryloyloxyethoxybenzophenone, 1g of azobisisobutyronitrile, 1g of triethylene glycol dimethacrylate, and 80g of ethyl acetate to form a 183g mixture, then add dropwise the mixture... The mixture was placed in a 500 mL four-necked flask equipped with a cooling reflux device, a dropping device, a thermometer, and a mechanical stirrer. The mixture was heated to 80 °C to initiate a free radical polymerization reaction. After the reaction was initiated, the reaction was exothermic. After the dropping was completed, the temperature was raised to 80–85 °C and the reaction was maintained for 3 hours to obtain an acrylate polymer solution. The solution was further distilled at atmospheric pressure at 120–140 °C for 1 hour to remove most of the organic solvent. Then, it was further distilled under reduced pressure at 140 °C to remove the organic solvent, resulting in a low surface energy UV-curable pressure-sensitive adhesive.
[0031] (2) The low surface energy adhesive obtained in step (1) is hot-melted at 130℃ using a UV-curable pressure-sensitive adhesive, and then applied at a concentration of 35 g / m². 2 The coating amount was applied to a PET film, and then cured by irradiation with a 200–408 nm ultraviolet light source to obtain a low surface energy UV-curable pressure-sensitive adhesive tape. Performance tests were conducted according to relevant testing methods, and the results are shown in Table 1.
[0032] Example 2:
[0033] (1) Mix 50g of 2-ethylhexyl acrylate, 20g of butyl acrylate, 7.5g of acrylic acid, 10g of vinyl acetate, 7.5g of 2-phenoxyethyl acrylate, 3.0g of polyethylene glycol methyl ether methacrylate (molecular weight 1600), 2.0g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.3g of n-dodecyl mercaptan, 0.3g of 4-acryloyloxyethoxybenzophenone, 0.5g of azobisisobutyronitrile, 0.5g of diethylene glycol dimethacrylate, and 70g of ethyl acetate to form 171.6g of [amount not specified]. The mixture was then added dropwise to a 500 mL four-necked flask equipped with a cooling reflux device, a dropper, a thermometer, and a mechanical stirrer. The mixture was heated to 80 °C to initiate a free radical polymerization reaction. After the initiation reaction, the reaction was exothermic. After the dropwise addition was completed, the temperature was raised to 73–80 °C and the reaction was maintained for 4 hours to obtain an acrylate polymer solution. The solution was further distilled at atmospheric pressure at 130–140 °C for 1 hour to remove most of the organic solvent. Then, it was further distilled under reduced pressure at 140 °C to remove the organic solvent, resulting in a low surface energy UV-curable pressure-sensitive adhesive.
[0034] (2) The low surface energy adhesive obtained in step (1) is hot-melted at 120℃ using a UV-curable pressure-sensitive adhesive, and then applied at a concentration of 35 g / m². 2 The coating amount was applied to a PET film, and then cured by irradiation with a 200–408 nm ultraviolet light source to obtain a low surface energy UV-curable pressure-sensitive adhesive tape. Performance tests were conducted according to relevant testing methods, and the results are shown in Table 1.
[0035] Example 3:
[0036] (1) Mix 50 g of 2-ethylhexyl acrylate, 20 g of ethyl acrylate, 7.5 g of methacrylic acid, 10 g of vinyl acetate, 7.5 g of ethyl methacrylate, 3 g of polyethylene glycol ethoxyacrylate (molecular weight 800), 2.0 g of 3-(trimethoxysilyl) propyl acrylate, 1.0 g of n-dodecyl mercaptan, 1.0 g of 4-acryloyloxyethoxybenzophenone, 1.0 g of azobisisobutyronitrile, 1.0 g of diethylene glycol dimethacrylate, and 90 g of ethyl acetate to form a 194 g mixture. Then, dropwise add the mixture into a 500 mL four-necked flask equipped with a cooling reflux device, a dropper, a thermometer, and a mechanical stirrer. Heat to 80 °C to initiate a free radical polymerization reaction. After the initiation reaction, the reaction is exothermic. After the dropwise addition is complete, raise the temperature to 73-80 °C and keep the reaction at that temperature for 5 h to obtain an acrylate polymer solution. Then, perform vacuum distillation at 140 °C to further remove the organic solvent to obtain a low surface energy UV-curable pressure-sensitive adhesive.
[0037] (2) The low surface energy adhesive obtained in step (1) is hot-melted at 120℃ using a UV-curable pressure-sensitive adhesive, and then applied at a concentration of 35 g / m². 2The coating amount was applied to a PET film, and then cured by irradiation with a 200–408 nm ultraviolet light source to obtain a low surface energy UV-curable pressure-sensitive adhesive tape. Performance tests were conducted according to relevant testing methods, and the results are shown in Table 1.
[0038] Example 4:
[0039] (1) Mix 45g isooctyl acrylate, 32g butyl acrylate, 7.5g acrylic acid, 5g phenoxyethyl acrylate, 6.5g methyl acrylate, 3g polyethylene glycol ethoxyacrylate (molecular weight 2000), 1.0g 3-(methacryloyloxy)propyltriethoxysilane, 1.0g n-dodecyl mercaptan, 1.2g 4-acryloyloxyethoxybenzophenone, 1.0g azobisisobutyronitrile, 1.5g triethylene glycol dimethacrylate, and 80g... Ethyl acetate was mixed to form a 184.7 g mixture, which was then added dropwise to a 500 mL four-necked flask equipped with a cooling reflux device, a dropper, a thermometer, and a mechanical stirrer. The mixture was heated to 80 °C to initiate a free radical polymerization reaction. After the initiation reaction, the reaction was exothermic. After the dropwise addition was completed, the temperature was raised to 75–90 °C and the reaction was maintained for 3 h to obtain an acrylate polymer solution. Then, the organic solvent was further removed by vacuum distillation at 135 °C to obtain a low surface energy UV-curable pressure-sensitive adhesive.
[0040] (2) The low surface energy adhesive obtained in step (1) is hot-melted at 120℃ using a UV-curable pressure-sensitive adhesive, and then applied at a concentration of 35 g / m². 2 The coating amount was applied to a PET film, and then cured by irradiation with a 200–408 nm ultraviolet light source to obtain a low surface energy UV-curable pressure-sensitive adhesive tape. Performance tests were conducted according to relevant testing methods, and the results are shown in Table 1.
[0041] Example 5:
[0042] (1) Mix 50g of 2-ethylhexyl acrylate, 20g of butyl acrylate, 7.5g of acrylic acid, 10g of vinyl acetate, 7.5g of 2-phenoxyethyl acrylate, 2g of polyethylene glycol acrylate (molecular weight 1000), 3.0g of 3-(methacryloyloxy)propyltrimethoxysilane, and 0.4g of n-dodecyl mercaptan, 0.4g of 4-acryloyloxyethoxybenzophenone, 0.6g of azobisisobutyronitrile, 0.6g of diethylene glycol dimethacrylate, 1 0.00 g of ethyl acetate was mixed to form a 202 g mixture. The mixture was then added dropwise into a 500 mL four-necked flask equipped with a cooling reflux device, a dropper, a thermometer, and a mechanical stirrer. The mixture was heated to 80 °C to initiate a free radical polymerization reaction. After the reaction was initiated, the reaction was exothermic. After the dropwise addition was completed, the temperature was raised to 75–90 °C and the reaction was maintained for 2 hours to obtain an acrylate polymer solution. The organic solvent was then further removed by vacuum distillation at 140 °C to obtain a low surface energy UV-curable pressure-sensitive adhesive.
[0043] (2) The low surface energy adhesive obtained in step (1) is hot-melted at 120℃ using a UV-curable pressure-sensitive adhesive, and then applied at a concentration of 35 g / m². 2 The coating amount was applied to a PET film, and then cured by irradiation with a 200–408 nm ultraviolet light source to obtain a low surface energy UV-curable pressure-sensitive adhesive tape. Performance tests were conducted according to relevant testing methods, and the results are shown in Table 1.
[0044] Comparative Example 1:
[0045] The difference between the comparative example and the embodiment is that silicone-modified acrylate and polyethylene glycol-modified acrylate are not added.
[0046] (1) Mix 50g of 2-ethylhexyl acrylate, 20g of butyl acrylate, 7.5g of acrylic acid, 10g of vinyl acetate, 7.5g of 2-phenoxyethyl acrylate, 0.4g of n-dodecyl mercaptan, 0.4g of 4-acryloyloxyethoxybenzophenone, 0.6g of azobisisobutyronitrile, 0.6g of diethylene glycol dimethacrylate, and 100g of ethyl acetate to form a 202g mixture. Then, dropwise add the mixture into a 500ml four-necked flask equipped with a cooling reflux device, a dropwise addition device, a thermometer, and a mechanical stirrer. Heat to 80℃ to initiate a free radical polymerization reaction. After the initiation reaction, the reaction is exothermic. After the dropwise addition is completed, raise the temperature to 75-90℃ and keep the reaction for 3h to obtain an acrylate polymer solution. Then, perform vacuum distillation at 140℃ to further remove the organic solvent to obtain a low surface energy UV-curable pressure-sensitive adhesive.
[0047] (2) The low surface energy adhesive obtained in step (1) is hot-melted at 125℃ using a UV-curable pressure-sensitive adhesive, and then applied at a concentration of 35 g / m². 2 The coating amount was applied to a PET film, and then cured by irradiation with a 200–408 nm ultraviolet light source to obtain a low surface energy UV-curable pressure-sensitive adhesive tape. Performance tests were conducted according to relevant testing methods, and the results are shown in Table 1.
[0048] Comparative Example 2:
[0049] (1) 49 g of isooctyl acrylate, 32 g of butyl acrylate, 7.5 g of acrylic acid, 5 g of 2-phenoxyethyl acrylate, 6.5 g of methyl acrylate, 1.0 g of n-dodecyl mercaptan, 1.2 g of 4-acryloyloxyethoxybenzophenone, 1.0 g of azobisisobutyronitrile, 1.5 g of triethylene glycol dimethacrylate, and 80 g of ethyl acetate were mixed to form a mixture of 184.7 g. The mixture was then added dropwise into a 500 mL four-necked flask equipped with a cooling reflux device, a dropper, a thermometer, and a mechanical stirrer. The mixture was heated to 80 °C to initiate a free radical polymerization reaction. After the initiation reaction, the reaction was exothermic. After the dropwise addition was completed, the temperature was raised to 75-90 °C and the reaction was maintained for 2 h to obtain an acrylate polymer solution. Then, the organic solvent was further removed by vacuum distillation at 140 °C to obtain a low surface energy UV-curable pressure-sensitive adhesive.
[0050] (2) The low surface energy adhesive obtained in step (1) is hot-melted at 120℃ using a UV-curable pressure-sensitive adhesive, and then applied at a concentration of 35 g / m². 2 The coating amount was applied to a PET film, and then cured by irradiation with a 200–408 nm ultraviolet light source to obtain a low surface energy UV-curable pressure-sensitive adhesive tape. Performance tests were conducted according to relevant testing methods, and the results are shown in Table 1.
[0051] Table 1: Performance test results of pressure-sensitive adhesive tape examples and comparative examples (25℃)
[0052]
[0053]
[0054] Notes: 1) HDPE: High-density polyethylene sheet, 3mm thick; SS: Stainless steel sheet; 2) - indicates that the test result is too small and no test result is displayed.
[0055] According to the test results in Table 1, the adhesive performance of the pressure-sensitive tape significantly improves with changes in light curing intensity, which expands its application range and product adaptability in the industrial field. A comparison of the adhesion performance of the examples and comparative examples on HDPE surfaces shows that the examples exhibit significantly enhanced adhesion to low surface energy materials, while the comparative examples show adhesive residue on steel plates, and the holding power is less than 24 hours. These results are mainly attributed to the molecular structure design of the samples, including the introduction of silicone-modified acrylates, polyethylene glycol-modified acrylates, and polyethylene glycol-modified crosslinking agents. By adjusting the flexibility of the molecular chains, reducing surface energy, and optimizing the degree of crosslinking, the adhesion performance to low surface energy materials is significantly improved. Cohesive strength is enhanced with increasing light intensity. Although peel strength and initial tack decrease, the holding power test results still exceed 168 hours. This invention provides new ideas and possibilities for the application of pressure-sensitive adhesives.
[0056] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A low surface energy UV-curable pressure-sensitive adhesive for bonding, characterized in that: The pressure-sensitive adhesive is prepared from the following raw materials: 100 parts by weight of acrylate copolymer raw material, 0.2-2 parts by weight of photoinitiator, 0.1-2 parts by weight of n-dodecyl mercaptan, 0.3-1.5 parts by weight of azobisisobutyronitrile, 0.5-2.5 parts by weight of crosslinking agent, and 70-100 parts by weight of ethyl acetate; wherein the 100 parts by weight of acrylate copolymer raw material is composed of 60-85 parts by weight of soft monomer, 5-15 parts by weight of hard monomer, 1-10 parts by weight of functional monomer, 1-10 parts by weight of silicone-modified acrylate, and 1-10 parts by weight of polyethylene glycol-modified acrylate; The organosilicon-modified acrylate is one or a mixture of more than one of 3-(methacryloyloxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltriethoxysilane, 3-(trimethoxysilyl)acrylate, 3-[tris(trimethylsiloxy)silyl]propyl methacrylate, and (3-acryloyloxypropyl)tris(trimethylsiloxy)silane; The polyethylene glycol modified acrylate has a molecular weight ≤2000, and is specifically one or a mixture of multiple of polyethylene glycol acrylate, polyethylene glycol methacrylate, polyethylene glycol methyl ether methacrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol ethoxy acrylate, and polyethylene glycol ethoxy methacrylate. The functional monomer is one or a mixture of two of acrylic acid and methacrylic acid; The preparation method of the low surface energy UV-curable pressure-sensitive adhesive is as follows: (1) Weigh 60-85 parts by weight of soft monomer, 5-15 parts by weight of hard monomer, 1-10 parts by weight of functional monomer, 1-10 parts by weight of organosilicon modified acrylate, 1-10 parts by weight of polyethylene glycol modified acrylate, 0.2-2 parts by weight of photoinitiator, 0.1-2 parts by weight of n-dodecyl mercaptan, 0.3-1.5 parts by weight of azobisisobutyronitrile, 0.5-2.5 parts by weight of crosslinking agent and mix them evenly with 70-100 parts by weight of ethyl acetate to obtain a mixture; (2) Add the mixture to the reactor at a uniform rate, raise the temperature to 65~90℃ to carry out free radical initiation polymerization, and after the addition is completed, keep the temperature at 75~90℃ for 2~5 h to obtain polymer solution; (3) The polymer solution was distilled under reduced pressure at 120~150℃ to remove ethyl acetate, and a low surface energy UV-curable pressure-sensitive adhesive was obtained.
2. The low surface energy UV-curable pressure-sensitive adhesive for adhesion according to claim 1, characterized in that: The soft monomer is one or a mixture of butyl acrylate and 2-ethylhexyl acrylate; The hard monomer is one or more of methyl acrylate, methyl methacrylate, ethyl methacrylate, vinyl acetate, and 2-phenoxyethyl acrylate.
3. The low surface energy UV-curable pressure-sensitive adhesive for adhesion according to claim 1, characterized in that: The crosslinking agent is one or a mixture of more of the following: diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol dimethacrylate, and tetraethylene glycol diacrylate.
4. The low surface energy UV-curable pressure-sensitive adhesive for adhesion according to claim 1, characterized in that: The photoinitiator is one or a mixture of two of 4-acryloyloxybenzophenone, 4-acryloyloxyethoxybenzophenone, and 4-acryloyloxy-2-hydroxybenzophenone.
5. The application of the low surface energy UV-curable pressure-sensitive adhesive according to claim 1 in hot melt pressure-sensitive adhesive tape products.
6. The application according to claim 5, characterized in that: The low surface energy adhesive UV-curable pressure-sensitive adhesive is hot-melted at 100~140℃, and then applied at a rate of 20~65 g / m². 2 The coating amount is applied to the thin film substrate and cured by irradiation with a 200~408 nm ultraviolet light source to obtain a low surface energy UV-curable pressure-sensitive adhesive tape product.
7. The application according to claim 6, characterized in that: The film substrate is a PET film or a BOPP film.
Citation Information
Patent Citations
Ultraviolet curing pressure-sensitive adhesive containing ultraviolet cross-linked tackifying resin and preparation method thereof
CN104673105A
Solvent-free light-cured organosilicone acrylate polymer pressure-sensitive adhesive and preparation method thereof
CN118546290A